Legal Protection of Indonesian Genetic Resources in Communal Intellectual Property Regime - Susanti, Susi; Tisnanta, HS; Putri, Ria Wierma (Institut Agama Islam Negeri Curup, 2024)
Indonesia, known as a Country with high biodiversity, faces significant challenges in protecting its genetic resources from the increasing threats of exploitation and biopiracy, often perpetrated by foreign entities exploiting Indonesia's genetic wealth without proper authorization or fair benefit-sharing. Therefore, it is crucial to analyze the legal protection of genetic resources in Indonesia as communal intellectual property, particularly in relation to the Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) and national efforts to protect genetic resources. This study employs a normative legal research method, examining various legal sources to address issues related to genetic resources. The research adopts a statutory and conceptual approach by analyzing existing legislation and the protection frameworks implemented in Indonesia for genetic resources. A qualitative analysis is further conducted by describing and interpreting various research sources to provide comprehensive answers to the research questions. The Result indicate that the TRIPS Agreement offers intellectual property protection standards that predominantly emphasize individual rights, failing to fully address the protection of communal intellectual property. In response to this limitation, Indonesia has implemented national policies, including Government Regulation No. 56 of 2022 and the Access and Benefit Sharing (ABS) mechanism. These policies aim to protect indigenous peoples' rights and ensure that the benefits derived from the utilization of genetic resources are distributed equitably. However, the implementation of these protections faces significant obstacles, such as weak institutional capacity, limited public awareness, and gaps in harmonization with international standards. To address these challenges, strategic measures are necessary, including strengthening cross-sector coordination, enhancing indigenous community education, and developing a more comprehensive benefit-sharing mechanism. These steps are essential to ensure that genetic resources are not only protected but also contribute sustainably to the nation’s welfare.